An empirical study on the asset-light operation and corporate performance of China's tourism listed companies - Shi Liang; Ruichao Yu; Zhenwei Liu; Wei Wang; Linrong Wu; Xuanming Hu (Heliyon, 2023)
Transitioning to an asset-light strategy is a significant shift for tourism companies in light of the global COVID-19 outbreak. This study investigates the impact of asset-light strategy on corporate performance using a sample of 588 firm-year observations from China A-share publicly traded tourism companies from 2003 to 2021. Using two-way fixed effects models, our results indicate that adopting an asset-light strategy can significantly improve the performance of tourism enterprises. We further verify that this influence mechanism is supply chain management using path analysis. More interestingly, the positive impact of asset-light strategy on enterprise performance is particularly significant in non-state-owned enterprises. Robustness tests with the system GMM method, the variable substitution method and the two-stage instrumental variables method support our main findings. The findings have significant ramifications for assisting the tourism industry, managers, and investors to strategically cope with settings that are complex and dynamic.